PENGARUH PERSEPSI RISIKO, DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN MELALUI VARIABEL KEPERCAYAAN PADA PENGGUNA JASA ANGKUTAN GOJEK DI BANDA ACEH PADA PANDEMI COVID-19 - Muhammad Raiyan; M Ridha Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
Abstract: This study aims to examine the influence of risk perception and service quality on customer satisfaction mediated by trust on Gojek users in Banda Aceh during the COVID-19 pandemic. The sample used in this study was 150 Gojek users in Banda Aceh using the Probability sampling techniques. Then, this study uses data collection equipment, namely a questionnaire (questionnaire). This study uses Structural Equation Modeling (SEM) as a method of analysis to determine the effect of the variables involved in mediation testing in this study. Based on the results of SEM analysis shows that risk perceptions have a significant negative effect on customer satisfaction, service quality has a significant positive effect on customer satisfaction, risk perception has a significant negative effect on trust, service quality has a significant positive effect on customer satisfaction, trust has a significant effect on customers, and trust is partially mediated between risk perception and service quality on customer satisfaction.